Innovative sensory strategies to improve learning of students with special educational needs - Lopez Romero, Yusibeth del Rocio (2025)
The study aimed to analyze the effectiveness of innovative sensory strategies to improve learning and inclusion of students with special educational needs in school settings. A qualitative, descriptive multiple-case study was conducted using a purposive sample of students with formally diagnosed sensory processing disorders. Semi-structured interviews and structured participant observation were employed to identify behavioral and emotional responses to planned sensory strategies. Findings showed improvements in classroom participation and adaptation to the educational environment, with increased interaction between peers and teachers. More stable emotional regulation and enhanced sustained attention during school tasks were also observed. Institutional analysis revealed differences linked to resource availability and specialized teacher training. It was concluded that the planned use of innovative sensory strategies facilitated inclusion and learning of students with special educational needs when adapted to individual characteristics and institutional conditions, highlighting the need for specific teacher training and adequate resources to ensure effectiveness.